Facilitating lesbian gay bisexual transgendered and intersexed youth-inclusive primary health care in Tshwane district Gauteng province South Africa : a constructivist grounded theory study - Van Wyk, Neltjie C. (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.